Phagotrophic Phytoflagellates across Ecosystems: Their Functional Role in the Southern Ocean and Mid-Atlantic Vernal Pools ... - Unkn Unknown (Temple University. Libraries, 2023)
Much of the world’s aquatic food webs and nutritional relationships have been blurred by the ever-increasing evidence that many phytoplankton are not exclusively heterotrophic or autotrophic, but instead mixotrophic. Mixotrophy is a continuum of different energy and carbon-acquisition mechanisms utilizing both autotrophy and heterotrophy which distorts the concept of single trophic tier modality. This makes mixotrophs flexible to adapt to environmental pressures and is becoming more the rule than the exception in many aquatic ecosystems. One unique environmental setting where mixotrophy could be highly beneficial to food web stability is in seasonally occurring ephemeral pools – aka vernal pools. Mid-Atlantic vernal pools are biodiverse biogeochemical hotspots and critical breeding habitats for a diverse number of endemic taxa including many endangered amphibian species. Vernal pools are not permanent standing bodies of water and have fluxes in hydrology, temperatures, nutrients, and irradiance to name a ...